Clinical characteristics of tuberculosis patients at Simpang Kawat Public Health Center, Jambi - Fitrianingsih, Fitrianingsih; Azzahra, Afifah; Maimum, Maimum (Riset Informasi Kesehatan, 2026)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis bacteria transmitted through the air. Based on World Health Organization (WHO) data in 2023, it is estimated that around 8.2 million of the world's population will suffer from TB. Based on the 2023 Indonesian health profile, the prevalence of new TB cases in Indonesia is 821,200 cases. In Jambi province, the highest TB prevalence is in Jambi City, approximately 209 per 100,000 population. This study aims to determine the clinical characteristics of TB patients at a Simpang Kawat Public Health Center, Jambi. Method: This was retrospective cross-sectional study using descriptive method at the Simpang Kawat Public Health Center in Jambi City. A total of TB patients was 60 patients. Secondary data was collected from medical records. Results: The results showed that the majority of TB patients consisted of 40-59 year (35%) age group, male (68.3%), employed (55%), married (73.3%), new cases (80%), first category treatment (100%), smokers (68.3%), and no comorbidities (73.3%). Conclusion: This study show that most of TB patients in public health center was sensitive TB patients with no comorbidities.